Antibiotics for lower respiratory tract infection in children presenting in primary care in England (ARTIC PC): a double-blind, randomised, placebo-controlled trial - Little, P; Francis, NA; Stuart, B; O'Reilly, G; Thompson, N; Becque, T; Hay, AD; Wang, K; Sharland, M; Harnden, A; Yao, G; Raftery, J; et al. (Elsevier, 2021)
Background: Antibiotic resistance is a global public health threat. Antibiotics are very commonly prescribed for children presenting with uncomplicated lower respiratory tract infections (LRTIs), but there is little evidence from randomised controlled trials of the effectiveness of antibiotics, both overall or among key clinical subgroups. In ARTIC PC, we assessed whether amoxicillin reduces the duration of moderately bad symptoms in children presenting with uncomplicated (non-pneumonic) LRTI in primary care, overall and in key clinical subgroups.